The introduction of critical care 'Outreach Outings' teaching as an example of compassionate leadership. - Habberfield, Lyndsay (British Journal of Nursing, 2026)
'Outreach Outings' is a ward-based teaching initiative, created by the Critical Care Outreach Team at University Hospitals Sussex NHS Foundation Trust. The aim is to increase the recognition and response to the deteriorating patient and bring deterioration teaching to all ward staff in 10-minute, bite-sized sessions. It is unique in that it operates 24/7 and is entirely multiprofessional and inclusive for all staff groups. Compassionate leadership involves a focus on relationships through careful listening, understanding, empathising and supporting. It enables those who are led to feel valued, respected and cared for, so they can reach their potential and enhance their work. This article explores the Outreach Outings project as an example of compassionate leadership, embodying autonomy, belonging and contribution: promoting education and knowledge to improve the recognition and response to the deteriorating patient.